The Challenges of the Tsangaya System of Education in Contemporary Nigeria (A case Study of Bauchi Emirate) - Umar, Aminu; Muhammad, Rabi’u Shehu; Muhammad, Abubakar; Abubakar, Muhammad Sani (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
The Tsangaya system of education is an Islamic-based educational system that had existed for several centuries in Northern Nigerian Muslim communities before the coming of the British colonial masters. The system has been the source of moral and educational training and had produced leaders, scholars, businessmen, and government functionaries with full support from the government. However, with the arrival of the British colonialist with a new system of education they suffered utmost neglect from the government which continued even after the so-called independence from the British colonialist. The objective of this paper is to examine the origin, development, and challenges facing the Tsangaya school system in Bauchi emirate, Bauchi state Nigeria using Historical and phenomenological methods. The paper’s findings among others revealed that the Tsangaya schools in the Bauchi emirate had suffered total neglect from both the government and other religious organizations and bodies. The paper recommends among other things that for the salvaging and resuscitation of the system there is a need for the government at all levels to join hands with religious bodies and or organizations. Key words: Tsangaya, Challenge, Bauchi Emirate, integration, almājiri